Stomatal Density of Jackfruit (Artocarpus heterophyllus Lamk.) Leaves as a Bioindicator of Urban Air Quality in Bandar Lampung - Rahmawati, Ayu; Nahari, Fadhilah Savana Nurun; Winandari, Ovi Prasetya (Indonesian Journal of Environment and Sustainability Issues, 2024)
Urban air pollution is a growing environmental concern, particularly in rapidly developing cities where vehicular emissions contribute significantly to deteriorating air quality. This study investigates the correlation between stomatal density in jackfruit (Artocarpus heterophyllus Lamk.) leaves and air quality in Bandar Lampung, focusing on two high-traffic urban locations: Sultan Agung Street and Pangeran Emir M Noer Street. Using a quantitative approach, leaf samples were collected through purposive sampling and analyzed for stomatal density using light microscopy (400× magnification). Concurrently, air quality was measured by assessing carbon monoxide (CO), nitrogen oxides (NOx), and particulate matter (PM10 and PM2.5) concentrations, which were compared against National Ambient Air Quality Standards (PP No. 41 of 1999). The results indicate a positive correlation between traffic intensity and stomatal density, suggesting that jackfruit trees increase stomatal density as an adaptive response to vehicular pollution. However, while enhanced stomatal density may improve CO₂ uptake for photosynthesis, excessive stomatal opening could lead to higher pollutant absorption, necessitating stomatal closure mechanisms during peak pollution periods. The findings confirm that jackfruit trees can serve as effective bioindicators for urban air pollution monitoring, given their physiological adaptability and widespread distribution in tropical urban settings. This research underscores the potential of plant-based bioindicators in sustainable air quality assessment and urban environmental management strategies.